DIVERSIFICATION OF BASED ON EHT NANGKA PROCESSED PRODUCTS (EASY, HEALTHY, TASTY) - Larasati, Meidina (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Kolaborasi Pengabdian Masyarakat UNDIP-UNNES 2019, 2020)
The availability of jackfruit in the village of Wanar is quite abundant. But the processing is still not optimal. The crop yields are not optimal enough to provide income for villagers because they are only sold raw to the market. From these problems, it is necessary to optimize the utilization of natural resources in the village of Wanar through product diversification efforts. The purpose of this activity is to provide skills in diversifying jackfruit processed into healthy and marketable products. This activity was carried out on October 18, 2019 at the Hall of the Village Hall of Wanar involving 25 target communities. The method used is interactive counseling and assistance / consultation with pre-activity stages, implementation, evaluation of knowledge and target motivation. The result of this activity is the improvement of jackfruit processing skills in this case the diversification of beverage powder and jackfruit jam products, and product marketing.